Èùʬ·¸¿ô¼Â´Ø¿ô f(x) ¤Ë¤Ä¤¤¤Æ¶Ë¸Â \[ \lim_{x \to a} {f(x) - f(a) \over x - a}= \lim_{\Delta x \to 0} {f(a+\Delta x) - f(a) \over \Delta x} , (x = a + \Delta x) \] ¤¬Â¸ºß¤¹¤ë¤È¤ f(x) ¤Ï x = a ¤Ë¤ª¤¤¤ÆÈùʬ²Äǽ(differentiable)¤Ç¤¢¤ë¤È¸À¤¤¤Þ¤¹¡£ ¤³¤Î¶Ë¸Â¤ò f¡ì(a) ¤È½ñ¤ x = a ¤Ë¤ª¤±¤ë f(x) ¤ÎÈùʬ·¸¿ô¤È¸À¤¤¤Þ¤¹¡£ ¸ø¼°\[(x^{a})′ = ax^{a−1}\] \[(sin x)′ = cos x\] \[(cos x)′ = −sin x\] \[ (\tan x)' = {1 \over \cos^2 x} = 1 + \tan^2 x \] \[(\arcsin x)'= {1 \over \sqrt{1-x^2}} \] \[(\arccos x)'= -{1 \over \sqrt{1-x^2}} \] \[(\arctan x)'= {1 \over 1+x^2} \] \[(e^{x})′ = e^{x}\] \[(a^{x})′ = log(a) a^{x}\] \[(\log x)'= {1 \over x} \] \[(\log_a x)'= {1 \over x \log a} \]
|